2017
DOI: 10.5539/jfr.v6n3p1
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus rhamnosus GG Inhibits BID Dependent-Apoptosis in Human Hepatocellular Carcinoma Cells Exposed to Patulin

Abstract: Patulin, a mycotoxin, which is a major contaminant in apple juices, has contributed immensely to the occurrence of liver diseases. Consumption of apple juice could over long period of time become harmful to the health of individuals with pre-existing liver disease. Probiotics are known for their role in patulin removal from aqueous media. In this study, we investigated the effects of a probiotic microorganism on patulin toxicity in hepatocellular carcinoma (HepG2) cells and established the protective effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…LGG is a widely used probiotic strain that has been evaluated for the treatment of diarrhea ( 138 ), antiproliferative effects on the cells of colon adenocarcinoma ( 139 ), suppressive effects on inflammation during Helicobacter infection in gastric adenocarcinoma cells ( 140 ), and high-fructose diet-induced NAFLD ( 141 ). In the present review, we found that probiotic LGG can decrease the risk of HCC through multiple pathways, including DNA damage ( 55 ), inflammatory and cell differentiation ( 56 ), and human hepatoma cell apoptotic regulation ( 58 ). Probiotics interact with the host and the microbiome via molecular effectors as metabolic products through the gastrointestinal microenvironment and mediate health benefits ( 142 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…LGG is a widely used probiotic strain that has been evaluated for the treatment of diarrhea ( 138 ), antiproliferative effects on the cells of colon adenocarcinoma ( 139 ), suppressive effects on inflammation during Helicobacter infection in gastric adenocarcinoma cells ( 140 ), and high-fructose diet-induced NAFLD ( 141 ). In the present review, we found that probiotic LGG can decrease the risk of HCC through multiple pathways, including DNA damage ( 55 ), inflammatory and cell differentiation ( 56 ), and human hepatoma cell apoptotic regulation ( 58 ). Probiotics interact with the host and the microbiome via molecular effectors as metabolic products through the gastrointestinal microenvironment and mediate health benefits ( 142 ).…”
Section: Discussionmentioning
confidence: 96%
“…There have been several in vitro investigations of the effects of This study reported the beneficial role of probiotics in the inhibition of liver fibrogenesis and the prevention of liver cancer. Another study has shown the protective effects of LGG against patulin-induced apoptosis in HepG2 cells by regulating the levels of proapoptotic BCL2 proteins p53 upregulated modulator of apoptosis and BH3-interacting domain death agonist in vitro (58).…”
Section: Probiotics In Hccmentioning
confidence: 99%